Acting but not reacting: Role of mindfulness in moderating the PCV-Deviance Relationship - SHAFFAKAT, Samah (Institutional Knowledge at Singapore Management University, 2017)
The current study examines processes through which the negative impact of perceived organizational violation on deviance could be curbed. Specifically, this study introduces mindfulness to the psychological contract literature to suggest that mindfulness, a dispositional, self-regulatory factor, could act as an emotional regulation aiding the reduction of employees’ negative responses to adverse events. Perceived contract violation has been shown to result in an intense negative reaction such as hostility and deviance, however, this study shows that mindfulness is germane in moderating this relationship. We find that employees high in mindfulness are more likely to be able to regulate their emotions, thoughts and behaviours and as such less likely to react negatively to perceived contract violation. Ultimately, we propose and examine a moderated-mediated model. Data collected across two studies demonstrate general support for the hypothesized relationships. We conclude with theoretical and practical implications as well as future research avenues.